Effect of chitosan on the antibacterial and physical properties of corn starch nanocomposite films. (23rd September 2016) - Ji, Na; Qin, Yang; Xi, Tingting; Xiong, Liu; Sun, Qingjie
Abstract : The influence of chitosan on the antibacterial and physical properties of corn starch nanocomposite films impregnated with calcium carbonate nanoparticles was investigated. With the increase of chitosan content, the nanocomposite films significantly enhanced antimicrobial activity against Escherichia coli, Staphylococcus aureus, and Bacillus cereus, and the films were more effective against gram‐negative bacteria. As chitosan content increased, the tensile strength of the nanocomposite films significantly increased from 2.24 to 10.71 MPa, and the highest elongation at break of the films was 134.31%, with the incorporation of chitosan at a 30% level. Fourier transform infrared spectra analysis revealed that hydrogen bonds were formed between the chitosan and the starch.